KAJIAN PENGELOLAAN PERSAMPAHAN DI KABUPATEN MUARA ENIM TAHUN 2024 - Devi, Silfiana; Bochori, Bochori; Nugrasyah, Amrillah; Anisah, Siti (LATERAL: Jurnal Teknik Sipil, 2025)
Waste is a major problem faced by Indonesia that must be resolved immediately. Along with the increasing population, consumption levels and technological advances are factors in the increasing amount of waste produced. Muara Enim Regency has 22 (twenty-two) Districts, currently the coverage of waste services has only reached 29.44%, only able to serve 2 (two) Districts, namely Muara Enim District and Lawang Kidul District under the supervision of the Muara Enim Waste UPTD and Lawang Kidul Waste UPTD, with 1 (one) existing Final Processing Site (TPA) namely the Bukit Kancil TPA located in Muara Enim City. Muara Enim District. Which causes low service coverage, waste handling percentage. This study aims to determine the right waste management to be implemented in Muara Enim Regency.